RESPONSES OF BLOOD PRESSURE IN YOUNG GUYS NORMOTENSIVE AFTER COMPLETION OF EXERCISE IN STATIONARY BIKE (Fiep Bulletin - online, 2015)
Introduction: Aerobic exercise causes different responses in the cardiovascular system.  Objective: To evaluate the blood pressure responses of normotensive young subjects underwent a workout performed on a stationary bicycle. Methodology: experimental, and randomized study conducted in LAFEX, conducted with 50 young individuals of both sexes, and were divided into 2 groups (Pbike; Pcontrol), 25 subjects for each group. For realization of Pbike, an stationary bike exercise Movement brand, R7 model was used. Individuals in the experimental protocol were evaluated by intensity of 65% HR reserve, while Pcontrole was at rest. BP was measured at the moments: pre-exercise, immediately after (T / 0), 15 minutes (T / 15), 30 minutes (T / 30) and 45 minutes after exercise completion (T / 45). For BP measurement, was used a semi-automatic machine, brand ONROM 705 IT . For statistical analysis SPSS software (version 20.0) was used. The assessment of data normality is given by the Kolmogorov-Smirnov test. For intergroup and intragroup analysis, the T-Student test, with p
Keywords: Blood pressure; Responses Of Blood Pressure; Aerobic exercise.